A systematic approach to the hip-spine relationship and its applications to total hip arthroplasty. (July 2019) - Eftekhary, N.; Shimmin, A.; Lazennec, J. Y.; Buckland, A.; Schwarzkopf, R.; Dorr, L. D.; Mayman, D.; Padgett, D.; Vigdorchik, J.
Abstract : There remains confusion in the literature with regard to the spinopelvic relationship, and its contribution to ideal acetabular component position. Critical assessment of the literature has been limited by use of conflicting terminology and definitions of new concepts that further confuse the topic. In 2017, the concept of a Hip-Spine Workgroup was created with the first meeting held at the American Academy of Orthopedic Surgeons Annual Meeting in 2018. The goal of this workgroup was to first help standardize terminology across the literature so that as a topic, multiple groups could produce literature that is immediately understandable and applicable. This consensus review from the Hip-Spine Workgroup aims to simplify the spinopelvic relationship, offer hip surgeons a concise summary of available literature, and select common terminology approved by both hip surgeons and spine surgeons for future research. Cite this article: Bone Joint J 2019;101-B:808–816.